Study of the competition tactics of Chinese and world top swimmers in recent years - Li , Z.; Yang, G.; Chen, A.; Liu, J.; Zhen, Z.; Li, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This abstract expounds on the tactical features and the differences of Chinese and World top swimmers based on the data of percentage of each split section collected in the recent Olympic Games and China National Games.